The parallels between COVID-19 and the Spanish flu of 1918 - Lyngdoh, Markordor (International Journal Of Community Medicine And Public Health, 2020)
The 1918 influenza pandemic was the most severe pandemic in recent history. It was caused by an H1N1 virus with genes of avian origin. On the other hand, the ongoing COVID-19 pandemic caused by a novel coronavirus hailed by the world health organization as a “once in a century health crisis” which has led to devastating impacts to health and livelihood the world over. The prevailing situation is reminiscent of the Spanish flu where definitive cure is unavailable and the public health measures like quarantine, social distancing, hand hygiene and isolation are the only alternatives. Both these diseases are transmitted through respiratory droplets, highly contagious and target the respiratory organs. The parallels between these two events cannot be denied. The Spanish flu thrived at a time when the knowledge and availability of antivirals and vaccine development were inadequate. This article strives to highlight a little more on these two separate pandemics and observe their similarities as well as their differences.